The impact of cost containment strategies on the financial performance of health insurance firms: case of PSMAS. - Mfarinya, Elizabeth T. (Midlands State University, 2017)
The research was prompted by the continual rising of costs and decreasing profitability of PSMAS, a health insurance firm in Zimbabwe. Despite the fact that the firm had made efforts to contain costs since 2013, its profitability and general financial performance continued to decline. The research therefore sought to identify and analyse the cost containment strategies being implemented by PSMAS and to establish factors that influence the success of these strategies. The research also aimed to establish the relationship that exists between cost containment strategies and the financial performance of health insurance firms. The study also had the objective of suggesting more effective strategies to curb costs as well as to determine other factors affecting the financial performance of health insurance firms like PSMAS. Literature from other authors and scholars that relate to the research was reviewed and explored. The researcher then made use of interviews and questionnaires to collect data for the research. A total of 32 questionnaires were distributed to the PSMAS staff and 27 were returned earning a response rate of 84% while three individuals were interviewed out of the five scheduled inspiring an interview response rate of 60%. Data collected was presented into tables and charts and analysis was made resulting in conclusions to be drawn. Recommendations were made based on the conclusions.